Valuing variance: the importance of variance analysis in clinical pathways utilisation - Hyett, K.; Podosky, M.; Santamaria, Nick; Ham, J. (Australian Healthcare and Hospitals Association, 2007)
Variations from the anticipated course of events in clinical pathways provide valuable information that could be used to improve clinical practice and health service planning. Surprisingly, variance data are rarely collected in health care organisations using clinical pathways. This paper describes a project which aimed toii improve reporting and analysis of variance data in a large regional and a smaller rural hospital using clinical pathways for a number of surgical, medical and obstetric procedures. The project used change management techniques and a variance analysis software program to inform clinical practice change